Characteristics and determinants by electricity consumption level of households in Korea - Min-Jeong Kim (Energy Reports, 2018)
This study divides the households into five groups according to the electricity consumption and compares the characteristics and the determinants of household electricity consumption for only two groups, the lowest and the highest. The data are drawn from a household energy consumption sample survey by Korea Energy Economics Institute in 2015. The results show the differences in socio-demographic, dwelling, and electricity consumption characteristics between two groups. Next, the factors affecting the household electricity consumption are investigated. Factor affecting the household electricity consumption for two groups is only the number of electrical appliances. There are also the differences in major determinants of the household electricity consumption for two groups. The results of this study would be useful for understanding socio-demographic, dwelling, and electricity consumption characteristics for two groups.
Keywords: 330; Household electricity consumption; Household energy consumption sample survey; Multiple regression; The fifth quintile; The first quintile